Relationship Between Body Composition and Balance Performance in Older Adults with Hyperkyphosis - Kantha, Phunsuk; Tsai, Shiow-Chwen; Hou, Chien-Wen; Yang, Rong-Sen; Su, Pei-Yu; Hsu, Wei-Li (Journal of medical and biological engineering, 2021)
Purpose Older adults with hyperkyphosis might have a high risk of falls since their whole body center of mass may shift to the boundary of the base of support. Body composition changes, such as low bone mineral content (BMC), decreased muscle mass, high body mass index (BMI), and increased fat mass are common in older adults with hyperkyphosis. This study aimed to investigate the relationship between body composition and balance performance using a biomechanical analysis in older adults with hyperkyphosis. Methods Thirty older adults with hyperkyphosis were recruited. BMC, muscle mass, BMI, and fat mass were measured for body composition. Balance performances were determined with walking, quiet standing, and forward reach. Gait speed, step length, center of mass–center of pressure inclination angle of heel strike (Inc-HS) and toe off (Inc-TO) during walking, center of mass–center of pressure inclination angle during quiet standing (Inc-QS), and reaching distance were calculated. Results BMC had a moderately positive correlation with gait speed (r = 0.48, p < 0.01) and a moderately positive correlation with step length (r = 0.43, p = 0.01). Muscle mass had a moderately positive correlation with step length (r = 0.41, p = 0.02), moderately positive correlation with Inc-HS (r = 0.36, p = 0.04), and moderately positive correlation with reaching distance (r = 0.43, p = 0.01). No significant correlations were found among BMI, fat mass and balance performance. Conclusion BMC and muscle mass should be considered as factors that might affect walking and forward reach in older adults with hyperkyphosis.